1989
DOI: 10.1152/ajpcell.1989.256.3.c591
|View full text |Cite
|
Sign up to set email alerts
|

Lack of endothelium-dependent relaxation in coronary resistance arteries of cholesterol-fed rabbits

Abstract: The endothelium-dependent contractile responses of subepicardial coronary resistance arteries (286 +/- 18 microns ID, n = 22) from rabbits fed either a 0.5 or 2.0% cholesterol-enriched diet or a control diet for 10-12 wk were determined under isometric conditions at the optimum length for active force production (Lo). After the development of tone with 29 mM K+-Krebs, arteries from control rabbits treated with acetylcholine (0.1-10 microM) showed a concentration-dependent relaxation, with a maximum decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(46 citation statements)
references
References 20 publications
3
43
0
Order By: Relevance
“…35 In contrast to the effect on PCs, SNP relaxed the DC segments of hypercholesterolemic rabbits similar to control segments, in agreement with other studies of the response to nitrovasodilators in small coronary arteries from cholesterol-fed animals. 26 - 27 Endothelial removal in segments of treated animals enhanced the relaxation to SNP as it did in control animals ( Figure 5), thus indicating that the basalfy released EDRF inhibiting the relaxation of the small coronary arteries to SNP was not affected by the hypercholesterolemia.…”
Section: Impaired Release From the Endothelium Of A Factor Inhibitingmentioning
confidence: 77%
See 2 more Smart Citations
“…35 In contrast to the effect on PCs, SNP relaxed the DC segments of hypercholesterolemic rabbits similar to control segments, in agreement with other studies of the response to nitrovasodilators in small coronary arteries from cholesterol-fed animals. 26 - 27 Endothelial removal in segments of treated animals enhanced the relaxation to SNP as it did in control animals ( Figure 5), thus indicating that the basalfy released EDRF inhibiting the relaxation of the small coronary arteries to SNP was not affected by the hypercholesterolemia.…”
Section: Impaired Release From the Endothelium Of A Factor Inhibitingmentioning
confidence: 77%
“…21 - 23 In direct contrast, others have reported unaltered endothelium-dependent vasodilation of the hind limb vasculature of the hypercholesterolemic rabbit 24 and unaltered cholinergic vasodilation of perfused kidneys of cholesterol-fed rabbits. 25 Third, although in vitro studies of isolated small coronary arteries from the hypercholesterolemic rabbit indicate impaired relaxation to ACh 26 as in atherosclerotic primates, 27 the findings are ambiguous. Angus and colleagues 28 found that the response to ACh of isolated, small coronary arteries from hypercholesterolemic rabbits was unaltered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Received October 29, 1992 revision accepted February 16, 1993. plaque-lined coronary arteries. 13 However, no data are available on leukocyte adherence to the coronary endothelium over the course of the hypercholesterolemic preplaque period. Moreover, the relation of adherence to EDRF production would also be of considerable interest.…”
Section: -9mentioning
confidence: 99%
“…2,9 In more advanced stages, the endothelium-independent relaxation, as assessed by the direct action of nitrovasodilators on arterial smooth muscle cells, can also be affected. [3][4][5][6][7][8][9][10][11]12 In addition, hyperlipidemia and atherosclerosis can be associated with abnormal vasoconstrictor responses. [13][14][15][16][17] Reduced ␣-adrenergic contractile responses but increased serotonergic contractile responses were reported in hyperlipidemic rabbits.…”
mentioning
confidence: 99%